Agonist-mediated activation of Bombyx mori diapause hormone receptor signals to extracellular signal-regulated kinases 1 and 2 through Gq-PLC-PKC-dependent cascade. (August 2016) - Jiang, Xue; Yang, Jingwen; Shen, Zhangfei; Chen, Yajie; Shi, Liangen; Zhou, Naiming
Abstract: Diapause is a developmental strategy adopted by insects to survive in challenging environments such as the low temperatures of a winter. This unique process is regulated by diapause hormone (DH), which is a neuropeptide hormone that induces egg diapause in Bombyx mori and is involved in terminating pupal diapause in heliothis moths. An G protein-coupled receptor from the silkworm, B . mori, has been identified as a specific cell surface receptor for DH. However, the detailed information on the DH-DHR system and its mechanism(s) involved in the induction of embryonic diapause remains unknown. Here, we combined functional assays with various specific inhibitors to elucidate the DHR-mediated signaling pathways. Upon activation by DH, B . mori DHR is coupled to the Gq protein, leading to a significant increase of intracellular Ca 2+ and cAMP response element-driven luciferase activity in an UBO-QIC, a specific Gq inhibitor, sensitive manner. B . mori DHR elicited ERK1/2 phosphorylation in a dose- and time-dependent manner in response to DH. This effect was almost completely inhibited by co-incubation with UBO-QIC and was also significantly suppressed by PLC inhibitor U73122, PKC inhibitors Gö6983 and the Ca 2+ chelator EGTA. Moreover, DHR-induced activation of ERK1/2 was significantly attenuated by treatment with the Gβγ specific inhibitors gallein and M119K and the PI3K specific inhibitor Wortmannin, but not by the Src specific inhibitor PP2. Our data also demonstrates that the EGFR-transactivation pathway is not involved in the DHR-mediated ERK1/2 phosphorylation. Future efforts are needed to clarify the role of the ERK1/2 signaling pathway in the DH-mediated induction of B . mori embryonic diapause. Graphical abstract: Highlights: Bombyx DHR is activated by DH via a Gq protein-dependent Pathway. Activated BmDHR induces ERK1/2 phosphorylation in a dose- and time-dependent manner. BmDHR triggers ERK1/2 activation through Gq-dependent cascade. Gβγ and PI3K are involved in BmDHR-mediated activation of ERK1/2. EGFR and Src are unlikely to implicate in BmDHR-induced ERK1/2 phosphorylation.